Simulation and Experimental Study on Rotor System Dynamic Analysis with the Blade-Coating Rubbing Faults - Xin Lu; Jie Tang; Liwen Wang (Shock and Vibration)
In the modern turbo-machinery, reducing the clearance between the blade tip and casing inner face is an effective method to improve the power performance, but the clearance reduction leads to increased risk of blade-casing rubbing. In this paper, a blade-coating rubbing force model which considered the abradable coating scraping is developed to simulate the rotor system dynamic characteristics at blade-casing rubbing faults with abradable coating. An experimental tester is established to simulate the rotor system blade-casing rubbing faults; the AlSi-ployphenyl ester abradable coating is prepared and introduced into the blade-casing experiment to verify the model. After the vibration and force analysis in simulation and experiment, the dynamic characteristics and the influence factors of blade-casing rubbing rotor system are studied.